Corrosion Inhibition of Carbon Steel in Oil and Gas Environments - Asmara, Y. P.; Sutjipto, A. G. E.; H. N. M., Zuki; Siregar, J. P.; Bachtiar, Dandi; T., Kurniawan; M. C., Ismail (IASE, 2016)
Oil-based corrosion inhibitors have been evaluated for carbon steel in 3.5% NaCl and saturated CO2 gas. The corrosion rate for carbon steel was determined based on the electro-chemical method using linear resistance polarization (LPR). Specimens at various inhibitor concentrations were placed in a beaker connected to a CO2 cylinder for CO2 gas bubbling. The corrosion test was conducted at room temperature and high temperature (60 oC and 80oC). Higher temperature conditions were used to study inhibitor stability. Results obtained from the LPR test indicated that the most effective corrosion inhibitor for carbon steel had between 5 to 100 ppm concentrations. The stability test showed that inhibitor efficiency was lower at higher temperature.